Ships without crews: IMO and UK responses to cybersecurity, technology, law and regulation of maritime autonomous surface ships (MASS) - Fenton, Adam James; Chapsos, Ioannis (Frontiers in Computer Science, 2023)
This article considers the current technological developments in uncrewed Maritime Autonomous Surface Ships (MASS), examines the legal and regulatory challenges that they raise, and describes the ways in which an international body (the International Maritime Organization, IMO) and a national agency (UK Maritime and Coastguard Agency, MCA) are engaging with the massive task of regulating this new development in shipping. To achieve the research aim, the article combines primary data from interviews with industry, government and international regulators, a survey completed by practitioners, experts and academics working in the field, and relevant secondary sources. The article makes an original contribution by noting and analysing the approaches of the IMO and the UK government – bodies which are highly influential in shaping global attitudes, preparation, adoption and responses to such innovative technologies like MASS – and how they have engaged with the difficult question of regulating the various legal, technical and cybersecurity challenges that they raise. It concludes that for the MASS technology to fulfil its potential and gradually see the integration of such vessels in international shipping in a safe, secure and sustainable way, the international community needs to work together, and update by consensus the key legal instruments and policy documents. In this major task, the UK approach and IOM’s leading role can play a protagonist role in developing best practice and implementing respectively.